Frequency of AFB smear and Gene Xpert positivity in bronchoalveolar lavage samples of smear-negative suspected pulmonary tuberculosis patients - Kumar, Jagdesh; Baqi, Abdul; Dayo, Abdul Rashid (Journal of Neonatal Surgery, 2025)
Background: TB is one of the most prevalent and fatal infectious illnesses in the world. Its early diagnosis and treatment is very important. Aim: The aim of this study was to find out the frequency of AFB smear and Gene Xpert positivity in bronchoalveolar lavage samples of smear-negative suspected pulmonary tuberculosis patients. Material and methods: The present cross-sectional study was carried out at Department of Pulmonology GMMMC Sukkur from January 2025 to June 2025 after taking approval from the ethical committee of the institute. Individuals of both genders and different age groups (ranged 20-70 years) clinically and radiologically suspected of having pulmonary tuberculosis, and negative for AFB on at least three consecutive sputum smear samples were included. All patients had bronchoscopies and BAL. BAL fluid was screened for Mycobacterium tuberculosis by AFB smear microscopy and GeneXpert MTB/RIF testing. The data was analyzed through SPSS version 23. Results: In the present study a total of 200 sputum smear-negative individuals with suspected pulmonary tuberculosis were examined out of which 122(61.0%) were male and 78 (39.0%) were females. The mean age of the study population was 48.2 ± 13.2 years (range: 20–70 years). 104 (41.6%) of the 250 BAL samples tested positive by AFB smear microscopy, whereas 146 (58.4%) were negative. In instance, GeneXpert MTB/RIF revealed Mycobacterium tuberculosis in 168 (67.2%) cases whereas 82 (32.8%) tested negative. Rural residents had much greater levels of AFB smear positive than urban residents. Whereas, GeneXpert positive on BAL was greater among unemployed than employed. A declining tendency in positivity was noted with a higher educational level, with uneducated participants expressing the most positivity (74.1%), which was of statistical significance (p = 0.04). Conclusion: The current study concluded that bronchoscopy with BAL significantly enhanced diagnostic yield in suspected TB individuals with negative sputum smears...